Anaemia in HIV-infected children: severity, types and effect on response to HAART. - Ruhinda, Eunice Nyesigire; Bajunirwe, Francis; Kiwanuka, Julius (BMC Pediatrics, 2012)
HIV and anaemia are major health challenges in Africa. Anaemia in HIV-infected individuals is associated with more rapid disease progression and a poorer prognosis if not addressed appropriately. This study aimed at determining the severity and types of anaemia among HIV infected children and its effect on short term response to antiretroviral therapy (ART).